The Osmolyte Ties That Bind: Genomic Insights Into Synthesis and Breakdown of Organic Osmolytes in Marine Microbes - McParland, Erin L.; Alexander, Harriet; Johnson, Winifred M. (Frontiers in Marine Science, 2021)
The production and consumption of organic matter by marine organisms plays a central role in the marine carbon cycle. Labile organic compounds (metabolites) are the major currency of energetic demands and organismal interaction, but these compounds remain elusive because of their rapid turnover and concomitant minuscule concentrations in the dissolved organic matter pool. Organic osmolytes are a group of small metabolites synthesized at high intracellular concentrations (mM) to regulate cellular osmolarity and have the potential to be released as abundant dissolved substrates. Osmolytes may represent an essential currency of exchange among heterotrophic prokaryotes and primary and secondary producers in marine food webs. For example, the well-known metabolite dimethylsulfoniopropionate (DMSP) is used as an osmolyte by some phytoplankton and can be subsequently metabolized by 60% of the marine bacterial community, supplying up to 13% of the bacterial carbon demand and 100% of the bacterial sulfur demand. While marine osmolytes have been studied for decades, our understanding of their cycling and significance within microbial communities is still far from comprehensive. Here, we surveyed the genes responsible for synthesis, breakdown, and transport of 14 key osmolytes. We systematically searched for these genes across marine bacterial genomes (n = 897) and protistan transcriptomes (n = 652) using homologous protein profiles to investigate the potential for osmolyte metabolisms. Using the pattern of gene presence and absence, we infer the metabolic potential of surveyed microbes to interact with each osmolyte. Specifically, we identify: (1) complete pathways for osmolyte synthesis in both prokaryotic and eukaryotic marine microbes, (2) microbes capable of transporting osmolytes but lacking complete synthesis and/or breakdown pathways, and (3) osmolytes whose synthesis and/or breakdown appears to be specialized and is limited to a subset of organisms. The analysis clearly demonstrates that the marine microbial loop has the genetic potential to actively recycle osmolytes and that this abundant group of small metabolites may function as a significant source of nutrients through exchange among diverse microbial groups that significantly contribute to the cycling of labile carbon.